PEMANFAATAN BUNGA TELANG DALAM PEMBUATAN LIP BALM - Sofia Daniati; Silvia Fatriana; Ifayatul Islamiyah; Hanida Asma Nafi’ah (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2021)
Telang flower is generally used as food coloring amd traditional medicine. The contents of telang flower has many benefits for humans. Also, it is hoped that the use of telang flower in the manufacture of lip balm will be a new innovation in cosmetic products. The aim of this research is to create a lip balm based on telang flower which functions to moisturize the lips. This research uses literature, ekasperiment, documentation, observation, and public teasting methods. This experiment resulted in two products with different compositions. In addition, that the two products have been tested publicly on 20 panelists ranging in age from 18 to 25 years. From 20 panelists who have tried 2 lip balm products. It was found that most pf them preferred products with a composition of 8 grams of teang flower extract, 50 grams of coconut oil, 30 grams of olive oil, 300 grams of beeswax, and 15 grams of ethanol. This can be seen from the public test average calculation score oh the favorite indicator, namely 2,5. Basade on the statemensts above, it can be concluded that the opporatunity to be developed as a new innovation in the world of cosmetics.